Major Current Problems Faced by Students in Dhaka: Causes, Implications, and Citizen Solutions. - Ahmed, Rashed (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This abstract explores the significant challenges faced by students in Dhaka, Bangladesh, focusing on their causes, implications, and potential citizen-driven solutions. The primary problems identified include inadequate educational infrastructure, characterized by overcrowded classrooms and insufficient resources, exacerbated by rapid urbanization and population growth. Moreover, the quality of education remains a critical concern due to outdated curricula, lack of qualified teachers, and a pervasive reliance on rote learning methods. These challenges have profound implications for students, leading to lower academic achievement, limited socio-economic mobility, and perpetuating cycles of poverty and inequality. Addressing these issues requires collaborative efforts involving citizens, communities, and policymakers. Citizen solutions may include grassroots initiatives to improve school facilities, advocacy for educational reforms, and programs to provide financial assistance and educational resources to disadvantaged students. By addressing these issues comprehensively, focusing on systemic reforms and community-driven interventions, Dhaka can foster an environment where all students have equitable access to quality education, enhancing their prospects for personal development and contributing to broader socio-economic development goals.